Chemical, biological and anatomical characterization of an extracellular matrix obtained from rabbit heart - Nieva, Eduardo Gabriel (2020)
Tissue Engineering is a discipline that works on biomaterials as scaffold to functional tissues been generated that restore, keep and improve damage organ or tissues. Tissue structure is essential, cells are responsible to keep and secrete their own support, named extracellular matrix. It’s organized into a three-dimensional ultrastructure, unique and specific for each tissue, interact individually with each cell and their environment through a dynamic reciprocity. Thus, an extracellular matrix generated by a decellularization process makes a proper scaffold to stem cells culture. The aim of this work is to get a cardiac descellularized extracellular matrix and their biochemical and anatomical characterization. Results show that our protocol of descelullarization is effective to get an acellular extracellular matrix preserved, showed by microscopy and with residual nucleic acids traces and with no cytotoxicity, which could be recellularized in further steps. Also, the methodology to achieve the descelullarization was used in the fastest and efficient way to get a three-dimensional preserved architecture.